Therapeutically targeting proinflammatory type I interferons in systemic lupus erythematosus: efficacy and insufficiency with a specific focus on lupus nephritis - Lai, Benjamin; Luo, Shue-Fen; Lai, Jenn-Haung (Frontiers in Immunology, 2024)
Type I interferons (IFN-Is) are important players in the immunopathogenesis of systemic lupus erythematosus (SLE). Pathogenic events in patients with SLE are potent triggers of IFN-I induction, yet IFN-I may induce or initiate the immunopathogenesis leading to these events. Because blocking IFN-I is effective in some clinical manifestations of SLE patients, concerns about the efficacy of anti-IFN-I therapy in patients with lupus nephritis remain. Tissues from kidney biopsies of patients with lupus nephritis revealed infiltration of various immune cells and activation of inflammatory signals; however, their correlation with renal damage is not clear, which raises serious concerns about how critical the role of IFN-I is among the potential contributors to the pathogenesis of lupus nephritis. This review addresses several issues related to the roles of IFN-I in SLE, especially in lupus nephritis, including (1) the contribution of IFN-I to the development and immunopathogenesis of SLE; (2) evidence supporting the association of IFN-I with lupus nephritis; (3) therapies targeting IFN-I and IFN-I downstream signaling molecules in SLE and lupus nephritis; (4) findings challenging the therapeutic benefits of anti-IFN-I in lupus nephritis; and (5) a perspective associated with anti-IFN-I biologics for lupus nephritis treatment. In addition to providing clear pictures of the roles of IFN-I in SLE, especially in lupus nephritis, this review addresses the lately published observations and clinical trials on this topic.